INTEGRATION OF CONTENT AND LANGUAGE INTEGRATED LEARNING ELEMENTS IN THE EDUCATION OF NONLINGUISTIC SPECIALTY STUDENTS BY MEANS OF INFORMATION TECHNOLOGIES - Kotova, Anna; Serdyuk, Victorya; Avdieienko, Iryna; Lenska, Olena; Ivaniga, Orina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article deals with the problem of CLIL elements integration when teaching students of non-linguistic specialities. Main approaches to the definition of this teaching method are given. It is found that different authors consider CLIL as an educational approach, special education techniques, flexible curricular etc., the main purpose of CLIL methodology is to create the link between the study of the foreign language and the content of the students’ major discipline. The necessity of the IT implementation into the educational process has been substantiated (it allows to reduce the unproductive costs of the teacher's labour, gives students wide scope to a freely choose their own trajectory, increases the efficiency and objectivity of monitoring and evaluating learning outcomes, promotes individualization of educational activities, etc.).We have to use IT technologies as they help improve and diversify students’ work. Precisely, when working with students we often use Moodle platform as it provides unlimited opportunities for both students and teachers. It is found that Moodle platform allows developing reading, listening, writing, and grammar skills. Some examples of how to work using Moodle platform is given in the article. It is shown that such parts of Moodle platform as Chat and Forum are of great interest for both foreign language teachers and students. For those students who officially work or are ill, the Assignment module is of particular interest.